Occurrence of Treponema DNA in equine hoof canker and normal hoof tissue. (9th October 2014) - Sykora, S.; Brandt, S.
Summary Reasons for performing study Equine hoof canker is a chronic pododermatitis of still unknown aetiology. Recent findings reported for 3 canker‐bearing individuals are suggestive for Treponema spp. having a role in disease pathogenesis. Objectives Based on this hypothesised association, we assessed a larger number of DNA samples from hooves with canker and normal hooves for the presence of treponemal DNA. Study design Retrospective survey of archived material. Methods The study involved 71 archival, PCR‐compatible DNA extractions purified from 59 canker samples obtained from 26 equine cases and from 12 hoof biopsies taken from 9 canker‐free control horses. Presence of treponemal DNA was assessed by qualitative PCR using 4 different primer pairs recognising in sum a broad range of Treponema ssp. Obtained amplification products were identified by bidirectional sequencing and BLAST alignment. Results Treponemal DNA was detected in 37 of 59 canker DNA samples from 19 of 26 cases and in 9 of 12 hoof DNA samples from 7 of 9 healthy individuals. Canine oral Treponema sp. and Treponema medium ssp. bovis were the most frequently detected treponemal sequences in hoof canker, while control tissues were mainly shown to harbour Treponema refringens‐like or canine oral Treponema‐like DNA. All control samples tested negative for T. medium ssp. bovis DNA. Conclusions Treponema DNA was detectable in the majority of hoof canker and control samples. The sample groups differed to some extent regarding identified Treponema phylotypes; however, this finding may be explained by the methodology used. Treponemes that are highly similar to bovine digital dermatitis treponemes are present in canker lesions. However, further work is needed to clarify the specific contribution of the identified Treponema phylotypes to the pathogenesis of disease.